Analysis of cell-free DNA concentration, fragmentation patterns and TP53 gene expression in mammary tumor-bearing dogs: A pilot study - Silvia Guil-Luna; Silvia Guil-Luna; Silvia Guil-Luna; Raquel Sánchez-Céspedes; Aurora Rivas Crespo; María Dolores Fernández; José Andrés Fernández Sarmiento; Antonio Rodríguez-Ariza; Antonio Rodríguez-Ariza; Yolanda Millán (Frontiers in Veterinary Science, 2023)
IntroductionLiquid biopsy based on the analysis of circulating cell-free DNA (cfDNA), as well as on detection of point mutations by digital droplet PCR (ddPCR), has revolutionized the research in oncology. In recent years, this technique has been pioneering in veterinary medicine since it is a minimally invasive approach with very promising results for characterization of tumors.MethodsThe aim of this study was, firstly, to analyze the concentration and the fragmentation pattern of cfDNA of dogs with mammary tumors (n = 36) and healthy dogs (n = 5) and its correlation with clinicopathological data. Secondly, analysis of TP53 gene expression and the point mutation in the codon 245 were performed in cfDNA and in tumor tissues to assess their potential as plasma biomarkers.Results and discussionOur results highlighted that those dogs with worse clinicopathological characteristics (simple or undifferentiated carcinomas, higher histological grade and presence of peritumoral inflammation) shown higher cfDNA concentration and higher concentrations of short-fragments (<190 bp) than healthy dogs. In addition, although no detection of the point mutation in codon 245 of TP53 gene could be detected neither in plasma nor tumor tissue, an increased TP53 expression was detected in animals with tumors bearing malignant characteristics. Finally, a high concordance with TP53 gene expression in plasma and tumor tissue and cfDNA concentration was also found. The results derived from this work confirm the valuable potential of cfDNA and its fragments, as well as the analysis of TP53 expression in plasma as useful liquid biomarkers for clinical application in veterinary oncology.